Severity and prognosis in intensive care : prospective application of the Apache II Index - Costa, Joel Isidoro; Amaral, José Luiz Gomes do; Munechika, Masashi; Juliano, Yara; Bezerra Filho, José Gomes (São Paulo Medical Journal, 1999)
CONTEXT: The performance of each ICU needs to be assessed within the overall context of medical care, as well as by the institution which the ICU forms part of. Evaluation mechanisms in the field of intensive care have been developed that are recognized worldwide within the scientific literature. OBJECTIVE: To study outcomes from groups of critical patients and to compare their actual and estimated mortality rates. DESIGN: Prospective study of patients' outcomes. SETTING: A tertiary care unit for a period of 13 months (anesthesiology intensive care unit at the Escola Paulista de Medicina). PARTICIPANTS: 520 patients selected according to sex, age and nature of hospitalization. DIAGNOSTIC TEST: The modified APACHE II prognostic index was applied in order to assess clinical severity and anticipation of mortality in three groups who had non-surgical treatment, emergency surgery and elective surgery. MAIN MEASUREMENTS: The APACHE II index. RESULTS: The application of this index allowed patients to be stratified and expected death risks for both subgroups and the entire sample population to be calculated. The observed mortality rate was greater than the expected rate (28.5% versus 23.6%, respectively), with a statistically significant difference. The standardized mortality rate was 1.20. Patients who obtained scores above 25 presented a significant outcome towards death. The most severe and worst evolving cases were, in decreasing order: non-surgical, emergency surgical and scheduled surgical patients; the actual general mortality rate was higher than the expected one. CONCLUSIONS: The use of the APACHE II index made it possible to stratify critical patient groups according to the severity of their condition.